Durability of Two-Component Grout in Tunneling Applications: A Laboratory Test Campaign - Carmine Todaro; Andrea Carigi; Daniele Peila (Geosciences)
Today, two-component grout is the most widely used backfilling technology in shielded mechanized tunneling. Despite its intensive use, however, very scant information pertaining to the durability of this material is available in the scientific literature. In this work, the aging of two-component grout is studied by curing grout samples using three different modalities. Furthermore, the action of air on two-component grout is studied by assessing the dehydration process, which is a phenomenon that occurs when the material is cured without being completely embedded in soil/rock. Uniaxial compression tests and three-point flexural tests have been carried out for mechanical characterization. The results reveal that in a curing environment made of sand, a moisture of 5% is sufficient to guarantee correct curing of the grout and extend the mechanical performance to three years, whereas the action of air is potentially dangerous, since the grout suffers strongly from dehydration. Despite this dehydration process, however, the mechanical performance of the grout also tends to increase for samples cured under the action of air until a very high level of cracking and shrinkage is reached. A discussion of the limitations on the uniaxial compression strength as the main mechanical parameter for the characterization of two-component grout concludes the work.